2010
DOI: 10.1088/0031-9155/55/16/004
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation from four-dimensional computed tomography: density versus Jacobian methods

Abstract: Two calculation methods to produce ventilation images from four-dimensional computed tomography (4DCT) acquired without added contrast have been reported. We reported a method to obtain ventilation images using deformable image registration (DIR) and the underlying CT density information. A second method performs the ventilation image calculation from the DIR result alone, using the Jacobian determinant of the deformation field to estimate the local volume changes resulting from ventilation. For each of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
296
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 171 publications
(306 citation statements)
references
References 49 publications
8
296
2
Order By: Relevance
“…CT ventilation imaging has the potential for widespread clinical implementation, as 4D-CT is routinely acquired for treatment planning at many centers [14] and ventilation computation only involves image processing/analysis without extra scans to patients. Additionally, CT ventilation imaging has a shorter scan time, higher spatial resolution (the exact resolution is unknown), lower cost, and/or greater availability than other modalities.Validation studies for CT ventilation imaging have been focused on cross-modality image comparisons [15][16][17][18][19][20][21][22]. For example, studies with mechanically ventilated sheep have demonstrated strong correlations between CT ventilation and xenon-CT ventilation [15,16].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CT ventilation imaging has the potential for widespread clinical implementation, as 4D-CT is routinely acquired for treatment planning at many centers [14] and ventilation computation only involves image processing/analysis without extra scans to patients. Additionally, CT ventilation imaging has a shorter scan time, higher spatial resolution (the exact resolution is unknown), lower cost, and/or greater availability than other modalities.Validation studies for CT ventilation imaging have been focused on cross-modality image comparisons [15][16][17][18][19][20][21][22]. For example, studies with mechanically ventilated sheep have demonstrated strong correlations between CT ventilation and xenon-CT ventilation [15,16].…”
mentioning
confidence: 99%
“…Validation studies for CT ventilation imaging have been focused on cross-modality image comparisons [15][16][17][18][19][20][21][22]. For example, studies with mechanically ventilated sheep have demonstrated strong correlations between CT ventilation and xenon-CT ventilation [15,16].…”
mentioning
confidence: 99%
“…Each patient's pre and post‐treatment 4DCT scan was used to calculate 4DCT‐ventilation maps using previously described methods 1, 2, 9. The lungs are first segmented on the 0% (Inhale) and 50% (Exhale) phases of the 4DCT data set.…”
Section: Methodsmentioning
confidence: 99%
“…The Jacobian is a mathematical method where volume change is estimated using the first derivative of the deformation field 13 , 24 , 32 , 33 . Local volume change of the lung is calculated using the Jacobian of the transformation that maps the end expiration phase of 4D CT image to the end inspiration phase.…”
Section: Methodsmentioning
confidence: 99%
“…Because of the different metrics between the two ventilation imaging modalities, namely density difference for the XeCT versus volume change for the ΔV method, the two ventilation distributions were converted to the relative percentile distribution (32) first and then the Dice similarity coefficient (DSC) (36) was applied to calculate the similarity between the two ventilation volumes. When volumes A and B are compared, DSC is calculated as,DSCfalse(A,Bfalse)=2×|AB||A|+|B|The values of DSC index range between 1.0 and 0.0.…”
Section: Methodsmentioning
confidence: 99%